2019
DOI: 10.3389/fnins.2019.00798
|View full text |Cite
|
Sign up to set email alerts
|

Aromatization Is Not Required for the Facilitation of Appetitive Sexual Behaviors in Ovariectomized Rats Treated With Estradiol and Testosterone

Abstract: Testosterone can be safely and effectively administered to estrogen-treated post-menopausal women experiencing hypoactive sexual desire. However, in the United States and Canada, although it is often administered off-label, testosterone co-administered with estradiol is not a federally approved treatment for sexual arousal/desire disorder, partly because its mechanism is poorly understood. One possible mechanism involves the aromatization of testosterone to estradiol. In an animal model, the administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 88 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…Although there is no threshold for any androgen that can be used to diagnose women with FSD, a recent meta-analysis concluded that there appears to be a moderate association between endogenous total testosterone levels and sexual desire [14]. Studies on female rats treated with estradiol, testosterone, and aromatase inhibitors first suggested that aromatization may not be necessary for testosterone to increase the sensitivity of the response to male-related cues [15]. These data were confirmed in subsequent experiments, in which the administration of the nonaromatizable androgen dihydrotestosterone (DHT) in estradiol-primed ovariectomized rats was able to enhance behavioral measures of sexual desire [16].…”
Section: Pathophysiology Of Low Desirementioning
confidence: 99%
“…Although there is no threshold for any androgen that can be used to diagnose women with FSD, a recent meta-analysis concluded that there appears to be a moderate association between endogenous total testosterone levels and sexual desire [14]. Studies on female rats treated with estradiol, testosterone, and aromatase inhibitors first suggested that aromatization may not be necessary for testosterone to increase the sensitivity of the response to male-related cues [15]. These data were confirmed in subsequent experiments, in which the administration of the nonaromatizable androgen dihydrotestosterone (DHT) in estradiol-primed ovariectomized rats was able to enhance behavioral measures of sexual desire [16].…”
Section: Pathophysiology Of Low Desirementioning
confidence: 99%